A study on the factors that influence employees work motivation in Sungai Petani Municipal Council / Nor Fatin Atiqah Abd Halim and Siti Nadia Rozali - Abd Halim, Nor Fatin Atiqah; Rozali, Siti Nadia (2018)
According to Mohammad & Anowar (2012) employee is the main driving force of any organisation that provides endless effort transform the decision that have being make by organisation into the action with the aim of achieving organizational goals. Therefore, workers are regarded as one thing that is supreme by organizational sources, and employee motivational issues have become a very important part of the human resource within the organization.